Measuring Innovation Everywhere: The Challenge of Better Policy, Learning, Evaluation and Monitoring - Fred Gault (Edward Elgar Publishing, 2020)
This book is about measuring innovation, not just in the business sector but in every sector of the economy, using, for the first time, an internationally agreed general definition of innovation. The resulting indicators can be used to inform policy development, and offer a better understanding of the impact of the innovation policy of governments, the strategy of businesses and the practice of households, in a more digital economy. Innovation is a systems phenomenon and systems provide a structure throughout the book.